Measuring - controlling complex for investigating the magnetic surfaces of the URAGAN-2M torsatron - Gubarev, S.P.; Ermakov, E.B.; Lesnyakov, G.G.; Maznichenko, S.M.; Opaleva, G.P.; Ozherel’ev, F.I.; Taran, V.S.; Tereshin, V.I.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2009)
Created hardware - software complex, intended for scan controlling with luminescent rod of magnetic surfaces in the poloidal cross-section of the torus (in the toroidal vacuum chamber), and investigating the structure of these surfaces in the URAGAN-2M torsatron are described.